Entrepreneurs’ Felt Responsibility for Constructive Change and Entrepreneurial Performance: A Moderated Mediation Model of Technology Action and Market Orientation - Du, Yuechao; Hu, Honghao; Wang, Zhongming (Frontiers in Psychology, 2021)
Drawing on self-determination theory, we examine the mechanism through which entrepreneurs’ felt responsibility for constructive change affects entrepreneurial performance and how market orientation affects the influencing mechanism. A questionnaire survey was conducted with 424 entrepreneurs of new ventures in China. The results show that entrepreneurs’ felt responsibility for constructive change is positively related to technology action and entrepreneurial performance and that technology action mediates the relationship between entrepreneurs’ felt responsibility for constructive change and entrepreneurial performance. In addition, market orientation moderates the relationship between technology action and entrepreneurial performance such that the relationship is stronger when the market orientation is stronger. Our findings suggest that when they feel responsibility for constructive change, entrepreneurs in high-tech industries tend to take technology actions to achieve their goals and improve the long-term development of ventures. It is also important for entrepreneurs to hold a market orientation, which helps them be aware of changes in customer needs rather than blindly focusing on the use of the latest technologies. Our study is a pioneer in exploring entrepreneurs’ felt responsibility for constructive change in the entrepreneurial context, advancing the research on entrepreneurship psychology. The paper further elucidates the behavioral mechanisms through which felt responsibility for constructive change affects entrepreneurial performance.